Correction: Seasonality and energetic impacts of castrating parasites on an estuarine mud crab along a salinity gradient - Sarah R. Greenberg; Darby L. Pochtar; April M.H. Blakeslee; Daniel Hanley; Amy E. Fowler (Marine Biology, 2026)

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Seasonality and energetic impacts of castrating parasites on an estuarine mud crab along a salinity gradient - Sarah R. Greenberg; Darby L. Pochtar; April M.H. Blakeslee; Daniel Hanley; Amy E. Fowler (Marine Biology, 2026)
Estuaries exhibit pronounced fluctuations in the abiotic environment, and salinity strongly structures species distribution, physiology, and biotic interactions, including hosts and their parasites. The white-fingered mud crab Rhithropanopeus harrisii is host to two macroparasites: the invasive rhizocephalan barnacle Loxothylacus panopaei and a recently described entoniscid isopod Cryptocancrion brevibrachium . To investigate how estuarine conditions shape this host-parasite system, we quantified the distribution, prevalence, and seasonality of both parasites over 18 months between 2021 and 2022 across nine sites spanning salinities ~ 1–20 in three tributaries of the Chesapeake Bay, USA. We further assessed parasitic impacts on host energetic and reproductive investment using hepatosomatic (HSI) and gonadosomatic (GSI) indices. Out of the 6,530 R. harrisii examined, the crabs only were found at sites with average salinities of ≤ 12.3. Cryptocancrion brevibrachium occurred at all sites with R. harrisii , where prevalence ranged from 0.4% to 39%, and was not influenced by salinity. In contrast, L. panopaei occurred at sites with salinities ≥ 8.7, and prevalence increased with salinity, reaching 80% at higher-salinity sites. Coinfections occurred only where the parasites’ salinity ranges overlapped (≥ 8.7). Prevalence and probability of infection for both parasites were highest between August and October, and R. harrisii between 7 and 8 mm carapace width were most likely to be infected. Both parasites significantly reduced host condition via lowered HSI and GSI, indicating substantial energetic and reproductive suppression. Our results demonstrate that salinity is a key driver of parasite distributions in R. harrisii , with distinctive patterns and impacts of each parasite on their shared host along a salinity gradient.

Predator functional response of the invasive white-fingered mud crab (Rhithropanopeus harrisii) in the Northern Baltic Sea across a salinity gradient - Sarah R. Goodnight; Veijo Jormalainen; Amy E. Fowler (Biological Invasions, 2026)
Salinity is a critical factor determining the impact and establishment of aquatic invasive species. We quantified the functional responses and prey consumption rates of the invasive mud crab Rhithropanopeus harrisii across a salinity gradient to evaluate how low salinity stress influences foraging in the northern Baltic Sea, and found significant differences in both attack rate ( a ) and handling time ( h ) across salinity treatments. Contrary to expectations of reduced feeding efficiency under osmotic stress, crabs in the lowest experimental salinity (2 ppt) exhibited the shortest handling times and highest feeding rates, more than doubling the prey consumption rates observed in the moderate salinity of 6 ppt. Female crabs also demonstrated higher attack rates, shorter handling times, and greater overall prey consumption than males, likely reflecting increased energetic demands during reproduction. These findings contrast with prior studies from southern Baltic populations, which reported reduced feeding performance at low salinities; potential hypotheses behind these results include population-level adaptation or pre-adaptation to local conditions and higher metabolic rates at low salinities due to osmoregulation. Our results indicate that this species is not only tolerant of but may thrive in fresher environments, positioning it well for persistence and expansion under predicted future climate-driven salinity shifts. Rhithropanopeus harrisii ’s high prey consumption capacity at low salinities poses an increasing threat to native benthic invertebrate communities, and female crabs specifically may impose a stronger foraging pressure than males. Our results highlight the salinity tolerance and ecological impact of this invasive predator, emphasizing its potential to alter invertebrate community dynamics in the Baltic Sea ecosystem .

Insights from three decades of IUCN Red List assessments catalyzing shark, ray, and chimaera conservation - Brittany Finucci; Cassandra L. Rigby; Nicholas K. Dulvy; Rachel D. Cavanagh; Sarah Fowler; Lucy R. Harrison; Julia M. Lawson; Riley Pollom; Colin A. Simpfendorfer; Rachel H. L. Walls; Rima W. Jabado (Conservation Biology, 2026)
The International Union for Conservation of Nature (IUCN) Red List of Threatened Species is a critical measure of global aquatic and terrestrial biodiversity status. It is also the basis for the Red List Index, which tracks extinction risk over time. Sharks, rays, and chimaeras (Chondrichthyes) have now been comprehensively assessed twice (1996–2011 and 2012–2021) with hindcast assessments from 1970 onward, yielding an unprecedented extinction risk trajectory for an aquatic vertebrate class. The three‐decade success of the IUCN Species Survival Commission (SSC) Shark Specialist Group (SSG) in providing updated and evidence‐based assessments stems from sustained and coordinated activities by SSG members. We examined how a community of dedicated experts organized to fill gaps in key information to inform Red List assessments. From this evaluation, we identified six key lessons related to membership, taxonomic changes, implementation of the precautionary approach, information prioritization, assessment standardization, and policy efforts. However, existing challenges, including resource constraints and assessment discrepancies at different spatial scales, need to be addressed to ensure Red List assessments stay on pace with advances in conservation. With the second global assessment of chondrichthyans completed, it is appropriate to reflect on the evolution of the SSG and its achievements over three decades to highlight new tools and approaches to red listing and to identify priorities for the immediate future that are also applicable to other aquatic taxa with limited data, slow life histories, and exposure to high levels of fishing.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

Trade regulations drive improved global shark and ray management - Mark E. Bond; Hollie Booth; Akshay Tanna; Sarah L. Fowler; Carlos J. Polo-Silva; K.H. Stanley Shea; Floriane Cardiec; Elisabeth F. Mansur; Rima W. Jabado (Marine Policy, 2025)

Caribbean Creep meets Chesapeake Creep: marine bioinvasions and community shifts along the Mid-Atlantic Coast, USA - Amy E. Fowler; April M. H. Blakeslee; Andrew Davinack; Robert Aguilar; Miranda Andersen; Clara Benadon; Henry H. C. Choong; Lindsay Green-Gavrielidis; Sarah R. Greenberg; El Hartshorn; Niels-Viggo Hobbs; Sara Labbe; et al. (Biological Invasions, 2025)
The Mid-Atlantic waters of North America are warming faster than > 90% of other global oceans, leading to significant increases in bottom water temperatures and influencing shifts in marine community structure. Given this modern-day scenario of significant community shifts over space and time, baseline surveys of species diversity are increasingly valuable. Therefore, we performed the first-ever marine bioinvasions Rapid Assessment Survey (RAS) along the Mid-Atlantic waters of the United States in June 2023, focused on marina floating pontoons in Virginia, Maryland, Delaware, and New Jersey. We recorded 29 non-indigenous, 16 cryptogenic, and 10 species that have expanded their ranges in the mid-Atlantic. Seven of these 10 species have expanded northwards from southern locations in the Caribbean (“Caribbean Creep”) or the western Atlantic (“Chesapeake Creep”), and three have expanded southwards. Five non-indigenous species (NIS) were found at more than 60% of the 10 sampled sites: the bryozoans Bugula neritina , Schizoporella pungens , Tricellaria inopinata, macroalgae Codium fragile subsp. fragile , and the sea anemone Aiptasiogeton eruptaurantia . We did not document any new nonindigenous species not already recorded on the Western Atlantic coast. All 10 communities were distinctly different, and species dominance varied by latitude and by site. This first-ever RAS of the Mid-Atlantic waters of the United States provides critical insight into how marine communities have been and are changing as a result of colonization by NIS, including those that have expanded their ranges as a result of human-induced climate change.

Understanding Motivators and Challenges to Enrollment in Maternal and Child Health and Nutrition Research: A Mixed Methods Study with Women of Child-Bearing Age and Clinical Practitioners - Alexandra MacMillan Uribe; Rebecca Seguin Fowler; Kelly Fisher; Erica Bender; Galen Eldridge; Margaret Demment; Regan Bailey; A. Catharine Ross; Diane Mitchell; Sarah Ray; Julie Gras-Najjar; Alexandra Early (Journal of Nutrition Education and Behavior, 2025)

Global assessment of manta and devil ray gill plate and meat trade: conservation implications and opportunities - Marta D. Palacios; Laura Weiand; Betty J. L. Laglbauer; Melissa R. Cronin; Sarah Fowler; Rima W. Jabado; Thanda Ko Gyi; Daniel Fernando; Godefroy De Bruyne; Stanley K. H. Shea; Paul Hilton; Yi-Li Gao; et al. (Environmental Biology of Fishes, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Self-swabbing versus assisted swabbing for viral detection by qRT-PCR: the experience from SARS-CoV-2 based on a meta-analysis of six prospectively designed evaluations conducted in a UK setting - Tom Fowler; David Chapman; Matthias E. Futschik; Sarah A. Tunkel; Edward Blandford; Elena Turek; Olumide Kolade; Sergio Souza da Cunha; Andrew Dodgson; Paul Klapper; Malur Sudhanva; Lindsey Davies; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose In April 2020, the UK Government implemented NHS Test and Trace to provide SARS-CoV-2 quantitative reverse transcription polymerase chain reaction (qRT-PCR) testing for the public, with nose-and-throat swabbing for samples performed by trained staff. Self-swabbing (SS) would allow rapid scale-up of testing capacity and access. Six studies were undertaken to determine whether SS was as effective for detecting SARS-CoV-2 as swabbing performed by trained staff. Methods Six prospective studies were conducted between April–October 2020, using six swab/media combinations. Differences between assisted swabbing (AS) and SS were evaluated for concordance, positivity, sensitivity, cycle threshold (Ct) values and void rates. Statistical analysis was performed using 95% confidence intervals (CIs), paired t-tests and model-based methods. Results Overall, 3,253 individuals were recruited (median age 37 years, 49% female), with 2,933 having valid paired qRT-PCR results. Pooled concordance rate was 98% (95% CI: 96%, 99%). Positivity rate differences for SS (8.1%) and AS (8.4%) and differences in pooled sensitivities between SS (86%; 95% CI: 78%, 92%) and AS (91%; 95% CI: 78%, 96%) were nonsignificant. Both types of swabbing led to pooled void rates below 2% and strongly correlated Ct values. Age, sex and previous swabbing experience did not have a significant impact on concordance or sensitivity. Conclusion The UK adopted a policy to promote self-testing for SARS-CoV-2 based on data demonstrating equivalence of SS versus AS. Positive outcomes with SS are likely generalisable to testing for other respiratory pathogens, and we consider self-sampling and self-testing essential for future pandemic preparedness.

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Mineral–water reactions in Earth’s mantle: Predictions from Born theory and ab initio molecular dynamics - Sarah J. Fowler; David M. Sherman; John P. Brodholt; Oliver T. Lord (Geochimica et Cosmochimica Acta, 2024)

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

A microcosm of modern crust formation: Evidence from zircon ages, Hf O and Nd Sr isotopes and bulk geochemistry of the Menglian Batholith, SE Tibet - Ren-Zhi Zhu; Shao-Cong Lai; Mike Fowler; Jin-Cheng Xie; Sarah M. Glynn (Chemical Geology, 2023)

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Putting sharks on the map: A global standard for improving shark area-based conservation - Ciaran A. Hyde; Giuseppe Notarbartolo di Sciara; Lynn Sorrentino; Charlotte Boyd; Brittany Finucci; Sarah L. Fowler; Peter M. Kyne; Guido Leurs; Colin A. Simpfendorfer; Michael J. Tetley; Freya Womersley; Rima W. Jabado (Frontiers in Marine Science, 2022)
Area-based conservation is essential to safeguard declining biodiversity. Several approaches have been developed for identifying networks of globally important areas based on the delineation of sites or seascapes of importance for various elements of biodiversity (e.g., birds, marine mammals). Sharks, rays, and chimaeras are facing a biodiversity crisis with an estimated 37% of species threatened with extinction driven by overfishing. Yet spatial planning tools often fail to consider the habitat needs critical for their survival. The Important Shark and Ray Area (ISRA) approach is proposed as a response to the dire global status of sharks, rays, and chimaeras. A set of four globally standardized scientific criteria, with seven sub-criteria, was developed based on input collated during four shark, biodiversity, and policy expert workshops conducted in 2022. The ISRA Criteria provide a framework to identify discrete, three-dimensional portions of habitat important for one or more shark, ray, or chimaera species, that have the potential to be delineated and managed for conservation. The ISRA Criteria can be applied to all environments where sharks occur (marine, estuarine, and freshwater) and consider the diversity of species, their complex behaviors and ecology, and biological needs. The identification of ISRAs will guide the development, design, and application of area-based conservation initiatives for sharks, rays, and chimaeras, and contribute to their recovery.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Patients with surgically treated culture-negative native joint septic arthritis have less severe disease and better outcomes - Ziv Paz; Mary Louise Fowler; Clara Zhu; Sarah B. Lieber; Andrew Moore; Robert H. Shmerling (Infectious Diseases, 2020)

Clinical characteristics and outcomes of patients with septic arthritis treated without surgery - Sarah B. Lieber; Noa Alpert; Mary Louise Fowler; Robert H. Shmerling; Ziv Paz (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Responding to Climate Change: Participatory Evaluation of Adaptation Options for Key Marine Fisheries in Australia’s South East - Emily Ogier; Sarah Jennings; Anthony Fowler; Stewart Frusher; Caleb Gardner; Paul Hamer; Alistair J. Hobday; Adrian Linanne; Stephan Mayfield; Craig Mundy; Andrew Sullivan; Geoff Tuck; et al. (Frontiers in Marine Science, 2020)

An Analytical Algorithm of Porosity–Permeability for Porous and Fractured Media: Extension to Reactive Transport Conditions and Fitting via Flow-Through Experiments Within Limestone and Dolomite - Selçuk Erol; Sarah Jane Fowler; Mathias Nehler; Eva De Boever; Virginie Harcouët-Menou; Ben Laenen (Transport in Porous Media, 2019)

Clinical characteristics of patients with polymicrobial septic arthritis - Orit Futterman; Sarah B. Lieber; Kunwal Nasrullah; Mary Louise Fowler; Robert H. Shmerling; Ziv Paz (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An Analytical Model of Porosity–Permeability for Porous and Fractured Media - Selçuk Erol; Sarah Jane Fowler; Virginie Harcouët-Menou; Ben Laenen (Transport in Porous Media, 2017)

Numerical Simulation of Reactive Fluid Flow on Unstructured Meshes - Sarah Jane Fowler; Georg Kosakowski; Thomas Driesner; Dmitrii A. Kulik; Thomas Wagner; Stefan Wilhelm; Olivier Masset (Transport in Porous Media, 2016)

The first field observation of intestinal eversion by a shark (broadnose sevengill, Notorynchus cepedianus) - Georgina Wiersma; Peter Verhoog; Sarah Fowler; Mark Meekan (Marine Biodiversity, 2016)

The role of CITES in the conservation of marine fishes subject to international trade - Amanda C J Vincent; Yvonne J Sadovy de Mitcheson; Sarah L Fowler; Susan Lieberman (Fish and Fisheries, 2014)
All possible tools need to be marshalled for marine fish conservation. Yet controversy has swirled around what role, if any, the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) should play for marine fishes. This paper analyses the relevance and applicability of CITES as a complementary tool for fisheries management. CITES currently regulates the international trade of very few marine fish species, by listing them in its Appendices. After the first meeting of the Parties (member countries) in 1976, no new marine fish taxa were added to the CITES Appendices until 2002, when Parties agreed to act to ensure sustainable and legal international trade in seahorses ( Hippocampus spp.) and two species of sharks. Progress has continued haltingly, adding only one more shark, humphead wrasse ( Cheilinus undulatus ) and sawfishes by 2012. Parties voice concerns that may include inadequate data, applicability of CITES listing criteria, roles of national fisheries agencies, enforcement challenges, CITES ' lack of experience with marine fishes, and/or identification and by‐catch problems. A common query is the relationship between CITES and other international agreements. Yet all these arguments can be countered, revealing CITES to be a relevant and appropriate instrument for promoting sound marine fisheries management. In reality, Parties that cannot implement CITES effectively for marine fishes will also need help to manage their fisheries sustainably. CITES action complements and supports other international fisheries management measures. As CITES engages with more marine fish listings, there will be greater scope to analyse its effectiveness in supporting different taxa in different contexts.

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Dry deposition of ammonia gas drives species change faster than wet deposition of ammonium ions: evidence from a long‐term field manipulation - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; John Neil Cape; Alan Crossley; Sarah Leeson; Mark A. Sutton; Netty van Dijk; David Fowler (Global Change Biology, 2011)
Although the effects of atmospheric nitrogen deposition on species composition are relatively well known, the roles of the different forms of nitrogen, in particular gaseous ammonia ( NH 3 ), have not been tested in the field. Since 2002, we have manipulated the form of N deposition to an ombrotrophic bog, W him, on deep peat in southern S cotland, with low ambient N (wet + dry = 8 kg N ha −1 yr −1 ) and S (4 kg S ha −1 yr −1 ) deposition. A gradient of ammonia ( NH 3 , dry N ), from 70 kg N ha −1 yr −1 down to background, 3–4 kg N ha −1 yr −1 was generated by free air release. Wet ammonium ( NH 4 + , wet N) was provided to replicate plots in a fine rainwater spray ( NH 4 Cl at +8, +24, +56 kg N ha −1 yr −1 ). Automated treatments are coupled to meteorological conditions, in a globally unique, field experiment. Ammonia concentrations were converted to NH 3 ‐ N deposition (kg N ha −1 ) using a site/vegetation specific parameterization. Within 3 years, exposure to relatively modest deposition of NH 3 , 20–56 kg NH 3 ‐N ha −1 yr −1 led to dramatic reductions in species cover, with almost total loss of C alluna vulgaris , S phagnum capillifolium and C ladonia portentosa . These effects appear to result from direct foliar uptake and interaction with abiotic and biotic stresses, rather than via effects on the soil. Additional wet N by contrast, significantly increased C alluna cover after 5 years at the 56 kg N dose, but reduced cover of S phagnum and C ladonia . Cover reductions caused by wet N were significantly different from and much smaller than those caused by equivalent dry N doses. The effects of gaseous NH 3 described here, highlight the potential for ammonia to destroy acid heathland and peat bog ecosystems. Separating the effects of gaseous ammonia and wet ammonium deposition, for a peat bog, has significant implications for regulatory bodies and conservation agencies.

Arabidopsis Transcriptional Activators CBF1, CBF2, and CBF3 have Matching Functional Activities - Sarah J. Gilmour; Sarah G. Fowler; Michael F. Thomashow (Plant Molecular Biology, 2004)